2020
DOI: 10.25122/jml-2019-0087
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitude of Iranian Youth Toward AIDS: A Systematic Review and Meta-Analysis in Iran

Abstract: Inadequate knowledge and negative attitudes are the major hindrances to prevent the spread of the human immunodeficiency virus. This study aims to assess the knowledge and attitude toward the human immunodeficiency virus and acquired immune deficiency syndrome among youths in Iran. We conducted a systematic review, searching online databases until July 2018, focusing on knowledge and attitudes about the human immunodeficiency virus and acquired immune deficiency syndrome in Iranian youths. We included the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The study used social cohesion for social capital measurement, divided into several variables: peer support, trust, and social participation, which were then divided into high and low levels. The study discovered that female social workers with a high score of social cohesion trust are more likely to perform HIV/AIDS prevention efforts by using a condom during sexual intercourse [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study used social cohesion for social capital measurement, divided into several variables: peer support, trust, and social participation, which were then divided into high and low levels. The study discovered that female social workers with a high score of social cohesion trust are more likely to perform HIV/AIDS prevention efforts by using a condom during sexual intercourse [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the mental and social capital level, most men perform HIV/AIDS prevention compared to those at the structural social capital level. Men are more open in discussing sex and reporting condom use more effectively in HIV/AIDS prevention [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is a clear negative attitude about these patients due to the fear of being infected (6). This separation and rejection cause a feeling of worthlessness in patients, and with loss of self-esteem, their life becomes more difficult (3), so that even patients in whom the disease has been largely controlled by proper treatment are still in a fragile situation (7). For this reason, the principle of dignity is much more important than the principle of life (6).…”
Section: Introductionmentioning
confidence: 99%
“…In a study entitled Health Care Neglect, Perceived Discrimination, and Dignity-related Distress among Chinese Patients with HIV in 2016, a significant correlation was found between physical and psychological symptoms, neglect in care, and perceived discrimination (8). The study of Momenabadi et al showed that most HIVinfected patients receive poor social support from family (7). A study by Shafi'i et al entitled Nurses' Performance and Attitudes in Dealing with HIV / AIDS Patients showed that although most nurses reported adherence to ethical commitments in caring for these patients, most had discriminatory attitudes and beliefs (9).…”
Section: Introductionmentioning
confidence: 99%